2014
DOI: 10.1270/jsbbs.64.222
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of ion-beam induced extremely late heading mutants in rice

Abstract: Two extremely late heading mutants were induced by ion beam irradiation in rice cultivar ‘Taichung 65’: KGM26 and KGM27. The F2 populations from the cross between the two mutants and Taichung 65 showed clear 3 early: 1 late segregation, suggesting control of late heading by a recessive gene. The genes identified in KGM26 and KGM27 were respectively designated as FLT1 and FLT2. The two genes were mapped using the crosses between the two mutants and an Indica cultivar ‘Kasalath’. FLT1 was located on the distal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…Our preliminary analysis revealed that these DNA markers have more than four alleles, which were difficult to distinguish from each other. Therefore, we used a closely linked Indel marker KGC9M8 ( Ichitani et al 2014 ) instead of E1828. The 40 DNA Indel markers in Supplemental Table 1 were used for this study.…”
Section: Methodsmentioning
confidence: 99%
“…Our preliminary analysis revealed that these DNA markers have more than four alleles, which were difficult to distinguish from each other. Therefore, we used a closely linked Indel marker KGC9M8 ( Ichitani et al 2014 ) instead of E1828. The 40 DNA Indel markers in Supplemental Table 1 were used for this study.…”
Section: Methodsmentioning
confidence: 99%
“…Mutation induction by gamma rays have been contributed for improving of crops (Ichitani et al, 2014;Parry et al, 2009;Oladosu et al, 2016;Mustikarini et al, 2016), this technique has played an influential role in increasing the world food security. Since new food crop varieties embedded with various induced mutations have contributed to the significant increase of crop production.…”
Section: Introductionmentioning
confidence: 99%
“…Induction mutation by gamma rays was successfully used for generating novel characteristics of direct importance in rice production and of potential quality and nutritional value (Ichitani et al, 2014;Parry et al, 2009;Oladosua et al, 2016). According to the data base of Atomic Energy Agency (IAEA), 3,222 officially released mutant varieties worldwide in more than 200 crop species (FAO/IAEA, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Hori et al, 2015;Lee and An 2015;Zhang et al, 2015;Zhan et al, 2015). Study on the structure of genes associated with response to photoperiod on flowering of rice has been reported by Nakamichi 2015 andYoshitake et al, 2015, which is triggered by day length (Ichitani et al, 2014) and is regulated by many genes (Itoh and Izawa 2013;Tsuji et al 2011), andEbana et al (2011) also reported as a negative control. Leaves of plants were taken from the plants grown in the greenhouse at PAIR -BATAN Jakarta in 2014.…”
Section: Introductionmentioning
confidence: 99%